Sosialisasi Dampak Sampah terhadap Lingkungan untuk Mewujudkan Lingkungan yang Bersih dan Sehat di Desa Harjowinangun Timur Kecamatan Tersono Kabupaten Batang - Naya Fatmawati Az Zahra; Aniq Muflihah; Ferdiaz Wicaksono; M Lulu Ilma’nun; M Lutfi Muzhaffar; Aunnur Rohman (Aksi Nyata : Jurnal Pengabdian Sosial dan Kemanusiaan, 2024)
Harjowinangun Timur Village is a village located in Tersono District, Batang Regency, Central Java Province, Indonesia. Harjowinangun Timur Village has a livelihood in agriculture and the majority of the people of Harjowinangun Timur Village work as farmers, farm laborers, and factory workers. Waste is one of the problems that occurs in Harjowinangun Timur Village. Waste is something that cannot be avoided and is difficult to solve, in an effort to reduce the waste population, the first thing to do is to increase public awareness about the dangers of waste. Therefore, the UIN Walisongo Religious Moderation Community Service (KKN) group has one work program that has urgency regarding this problem, namely conducting socialization of waste and the impact of waste on the environment to create a clean and healthy environment. With the socialization program of waste and the impact of waste on the environment to create a clean and healthy environment in Harjowinangun Timur Village, it is hoped that the environmental conditions of Harjowinangun Timur Village will improve and can overcome the waste problem in Harjowinangun Timur Village